Nurses [videorecording (DVD)] : if Florence could see us now - Douglas, Kathy (Registered nurse); Madril, Sara Moncada; Madril, Sara Moncada (First Run Features, 2013)
Looks at the challenges and rewards of being a nurse. Nurses working in a variety of specialties share their experiences and reflect on the profession.